Region Stavropol, Russland/Region Kachetien, Georgien. Umweltarchive und Archäologie im Kaukasus: Neue Methoden in der archäologischen Klimaforschung. Die Arbeiten des Jahres 2020 - Reinhold, Sabine; Schlotzhauer, Udo; Hansen, Svend; Heinrich, Ingo (e-Forschungsberichte des DAI, 2021)
In 2020, a pioneering step was taken towards the development of high-precision climate data in the Northern Caucasus. Groundwork was laid for a cooperation of various partners, which also methodologically contributes fundamentally new components to climate research in the region. Up to now, reconstructions of environmental changes in the Caucasus have been based primarily on geoarchives. However, the systematic dendroclimatological investigation of wood from Bronze Age burial chambers in cooperation with the GFZ Potsdam will open up new methodological territory, all the more so as the cooperation with the Beuth University of Applied Sciences provides a measuring instrument that allows new access to images resolved down to the cell level.